Принцип мікропрограмного керування та автоматизація проектування операційних пристроїв. ІІ - Петрушенко, А.М. (Control systems & computers, 2020)
Розглядається один із можливих підходів до вирішення на базі принципу мікропрограмного керування проблеми комплексної – від постановки задачі до отримання ескіза друкованої плати – автоматизації процесу розробки операційних пристроїв. Підхід демонструється на прикладі синтезу в діалоговій трансформаційній машині – інструментарії алгебро-граматичних методів подання знань у різноманітних предметних областях – керуючого автомата операційного пристрою, що реалізує операцію додавання. Цель данной статьи — демонстрация одного из возможных подходов к реализации инструментария, воплощающего модель математизации В.М. Глушкова, и его (инструментария) возможностей на примере синтеза операционных устройств. Методы. При реализации инструментария и алгоритма синтеза операционных устройств использовался алгебро-грамматический метод представления знаний, метод построения операционных устройств на базе принципа микропрограммного управления, методы абстрактной и структурной теории автоматов, методы алгебры алгоритмов и т.д. Результаты. Разработан инструментарий, воплощающий модель математизации В.М. Глушкова и позволяющий осуществить комплексную автоматизацию проектирования операционных устройств. The purpose is to demonstrate the inextricable link between the fundamental concepts of the general theory of computer systems design and practical methods of designing software and hardware of computer technology, as well as new technological capabilities that arise when using the apparatus of algebra of algorithms in the process of designing programmes and equipment using an interactive transformational machine. M ethods. When implementing the tools (conversational transformation machine) and the synthesis algorithm of operating devices, we used the algebraic-grammatical method of representing knowledge, the method of constructing operating devices based on the principle of microprogram control, the methods of abstract and structural theory of automata, the methods of algebra of algorithms, etc. Results. Synthesis methods for operating devices developed for the language of graph diagrams of algorithms and the language of logical diagrams of algorithms are extended to the language CAA \ D – the input language of the dialogue transformation machine. Based on the dialogue transformational machine, a toolkit has been developed that embodies the V.M. Glushkov mathematical model and allows the complex automation of the operating devices: from setting the task to obtaining a sketch of the printed circuit board.